Microbial community structure and occurrence of diverse autotrophic ammonium oxidizing microorganisms in the anammox process - Bae, H.; Chung, Y. -C.; Jung, J. -Y. (IWA PUBLISHING, 2010)
The enrichment of anaerobic ammonium oxidizing (anammox) bacteria using an upflow anaerobic sludge bioreactor was successfully conducted for 400 days of continuous operation. The bacterial community structure of anammox bioreactor included Proteobacteria (42%), Chloroflexi (22%), Planctomycetes (20%), Chlorobi (7%), Bacteroidetes (5%), Acidobacteria (2%), and Actinobacteria (2%). All clones of Planctomycetes were affiliated with the anammox bacteria, Planctomycete KSU-1 (AB057453). The presence and diversity of ammonia oxidizing bacteria (AOB) and archaea (AOA) were identified by terminal restriction fragment length polymorphism (T-RFLP) based on the amoA gene sequences. The AOB in anammox bioreactor were affiliated with the Nitrosomonas europaea cluster. The T-RFLP result of AOA showed the diverse microbial community structure of AOA with three terminal restriction fragments (T-RFs).
Keywords: ROTATING BIOLOGICAL CONTACTOR; SP-NOV.; ACTIVATED-SLUDGE; WASTE-WATER; GEN. NOV.; ARCHAEA; BACTERIA; SEQUENCES; BIOFILM; TOOL